Ecological risks assessment of fishery commodities from heavy metal in The East Java Province, Indonesia - Andriyono, Sapto; Hidayati, Nuning Vita; Fitrani, Mirna; A. Manaf, Latifah; Habib, Ahasan; Dewi, Umi U.; Mukadar, Saadah (Polish Academy of Sciences Publishing House, 2024)
Heavy metals are a crucial group of chemicals extensively used in materials to meet human needs, eventually leading to contamination of aquatic ecosystems and accumulation in organism’s tissues. Heavy metals enter the aquatic ecosystem from various sources. Those metals that pollute aquatic waters are deposited in sediments, remain dissolved in water or accumulate in the food web of aquatic organisms. Benthic biota is believed to accumulate the highest levels of these metals, while other aquatic animals, such as fish, shrimp, and macroalgae, serve as significant sources of heavy metals intake through food and the environmental exposure. Ina study conducted in and around the east Java, Indonesia, the concentration of heavy metals in commercially important fish species, shellfish, and macroalgae were evaluated using an inductive couple plasma-mass spectrometer (ICP-MS). This study is very important because fishery resources are not only vital for exports but also serve as a primary source of essential food for local communities. The results showed that heavy metal concentration (Pb, Cd, and Hg) in samples were 12.3 mg∙dm–3, 0.171 mg∙dm–3, and undetectable, respectively. This study showed that different metals were present in the samples at different levels, all of which fell within the maximum residual levels set by the EU and USFDA. The results of an analysis of food safety based on the Hazard Index showed values below 1 point, indicating that fishery products (fish, shrimp, and macroalgae) from the East Java Province are generally safe for human consumption. © 2024. The Authors.